2015
DOI: 10.1111/bph.12959
|View full text |Cite
|
Sign up to set email alerts
|

The cGMP/PKG pathway as a common mediator of cardioprotection: translatability and mechanism

Abstract: Cardiomyocyte cell death occurring during myocardial reperfusion (reperfusion injury) contributes to final infarct size after transient coronary occlusion. Different interrelated mechanisms of reperfusion injury have been identified, including alterations in cytosolic Ca 2+ handling, sarcoplasmic reticulum-mediated Ca 2+ oscillations and hypercontracture, proteolysis secondary to calpain activation and mitochondrial permeability transition. All these mechanisms occur during the initial minutes of reperfusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 148 publications
(155 reference statements)
0
64
2
2
Order By: Relevance
“…However, according to the results presented by Seya and coauthors , S ‐nitrosoacetylpenacillamine (SNAP) or 8‐Bromo‐cGMP stimulated calcium‐dependent CytC release and apoptosis, while the inhibitors of NOS, GC, and PKG prevented these effects. These results contradict the generally admitted prosurvival action of cytosolic NOS/GC/PKG1 signaling system involved in the prevention of mPTP opening and cell death .…”
Section: Introductioncontrasting
confidence: 78%
See 1 more Smart Citation
“…However, according to the results presented by Seya and coauthors , S ‐nitrosoacetylpenacillamine (SNAP) or 8‐Bromo‐cGMP stimulated calcium‐dependent CytC release and apoptosis, while the inhibitors of NOS, GC, and PKG prevented these effects. These results contradict the generally admitted prosurvival action of cytosolic NOS/GC/PKG1 signaling system involved in the prevention of mPTP opening and cell death .…”
Section: Introductioncontrasting
confidence: 78%
“…Mitochondrial permeability transition pore is considered as a common pathway leading to the development of apoptosis and necrosis, which are observed in myocardial ischemia/reperfusion (I/R) , acute steatohepatitis, and oxidative stress , and under the action of various drugs and toxins . Calcium and reactive oxygen species are recognized as key mediators involved in mPTP opening .…”
Section: Introductionmentioning
confidence: 99%
“…However, according to 4 the results presented by Seya and coauthors [23], SNAP or 8-Bromo-cGMP induced calciumdependent CytC release and apoptosis, while the inhibitors of NOS, GC, and PKG prevented these effects. These results contradict to the generally admitted pro-survival action of cytosolic NOS/GC/PKG1-SS directed at the prevention of MPTP opening and cell death [26][27][28][29].…”
Section: Introductioncontrasting
confidence: 61%
“…MPTP is considered as a common pathway leading to the development of apoptosis and necrosis, which are observed in myocardial ischaemia-reperfusion (I/R) [28][29][30][31][32][33][34], acute steatohepatits and oxidative stress [31,35,36], and under the action of various drugs and toxins [31,37]. Calcium and reactive oxygen species (ROS) are recognized as key mediators involved in MPTP opening [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our experiment results revealed that upregulated SLC8A1‐AS1 exhibited notably elevated mRNA and protein levels of PKG1, PKG2, ANP, and BNP, indicating that the overexpression of SLC8A1‐AS1 could act to reversely downregulate the expression levels of genes related to the cGMP‐PKG pathway induced by SLC8A1 overexpression. Evidence has been presented suggesting that the cGMP/PKG pathway is a common mediator of cardioprotection and modulation of the cGMP/PKG pathway highlighting its potential as a therapeutic target for MI (Inserte & Garcia‐Dorado, ). A previous study provided verification indicating that the cGMP/PKG signaling pathway contributes to myocardial postconditioning protection to a certain degree (Inserte et al, ).…”
Section: Discussionmentioning
confidence: 99%